2007
DOI: 10.1017/s1481803500015529
|View full text |Cite
|
Sign up to set email alerts
|

Myth: Nephrolithiasis and medical expulsive therapy

Abstract: There is a medical myth that ureteral stones larger than 5 mm will not pass spontaneously and require urological intervention for removal. Recent findings indicate that medical expulsive therapy can facilitate spontaneous passage for stones up to 10 mm. For the management of ureteral stones, we recommend administering tamsulosin and a corticosteroid (deflazacort or prednisone) along with the standard therapy of analgesics, antibiotics and hydration. RÉSUMÉSelon un mythe médical, les calculs urétéraux de plus d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Calcium-channel blockers, by modifying the effect of calcium on smooth muscle cells of the ureter, have been proposed to decrease ureteral contractions and, subsequently, the pain of ureteral colic. [526] The ureter contains both alpha- and beta-adrenergic receptors. Antagonists of the alpha-1-adrenergic receptor, in particular, inhibit basal tone and decrease peristaltic frequency and amplitude with the consequences of increased fluid transport and decreased intra-ureteral pressure; they also block the conduction of visceral referred pain to the central nervous system, acting on C-fibres or sympathetic postganglionic neurons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium-channel blockers, by modifying the effect of calcium on smooth muscle cells of the ureter, have been proposed to decrease ureteral contractions and, subsequently, the pain of ureteral colic. [526] The ureter contains both alpha- and beta-adrenergic receptors. Antagonists of the alpha-1-adrenergic receptor, in particular, inhibit basal tone and decrease peristaltic frequency and amplitude with the consequences of increased fluid transport and decreased intra-ureteral pressure; they also block the conduction of visceral referred pain to the central nervous system, acting on C-fibres or sympathetic postganglionic neurons.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently used anti-inflammatory drugs in this context are corticosteroids, which are given in association with alpha-1-adrenergic receptor antagonists and calcium-channel blockers because of their action of decreasing edema and inflammation and, thereby, relieving an obstacle to the passage of the stone. [263032] Corticosteroids should, however, only be used for short periods in order to avoid the many adverse effects associated with prolonged therapy. [33] The role of corticosteroid therapy alone has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Investigators have shown that larger stones tend to cause more intense inflammatory reactions leading to edema. [ 5 ] Corticosteroids stabilize neutrophil lysosomes, therefore, decreasing inflammation and edema related to mechanical irritation. [ 6 7 ] Here, we have administered 30 mg of deflazacort for 10 days.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the authors recommended not to use for more than 10 days to prevent the side effects of prolonged use. [ 5 8 9 10 ] In our clinical practice, we are not routinely using deflazacort for MET because of its high cost and also as it limit the duration of MET. In the present study, we observed that the inflamed ureteric orifice appears as prominent soft tissue swelling on CT scan [ Figure 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover MET cannot be given for a prolonged period. May et al [4] had suggested that any MET should not be indiscriminately given beyond 4 weeks, as continuous treatment with MET would cause renal dysfunction, further pain and probably urosepsis.…”
Section: Discussionmentioning
confidence: 99%